Clinical and biological determinants of P-wave duration: cross-sectional data from the population-based CoLaus|PsyCoLaus study - Pedro Marques-Vidal; Peter Vollenweider; Federica Bocchi; Etienne Pruvot; Gerard Waeber; David Gachoud (BMJ Open, 2020)
Objectives P-wave duration (PWD) is associated with the development of atrial arrhythmias, cardiovascular and all-cause mortality. With this study, we aimed to assess the distribution and determinants of PWD in the general population.Design Cross-sectional study using data collected between 2014 and 2016.Setting In the population-based cohort CoLaus|PsyCoLaus, Lausanne, Switzerland, we used 12-lead ECGs to measure PWD. Potential demographic, clinical and biological determinants of PWD were collected by questionnaire, anthropometry, blood pressure measurement and biological assays.Participants Data from 3459 participants (55% women, 62±10 years, 93% Caucasian) were included. Participants were excluded if they presented with (1) no sinus rhythm or paced rhythm on the study ECG or Wolff-Parkinson-White ECG pattern; (2) missing or non-interpretable ECG; and (3) missing phenotypic data.Primary outcome measure Determine (1) the PWD distribution and (2) the demographic, clinical and biological determinants of PWD in a large population-based cohort.Results Median and IQR of PWD was 112 (102–120) ms . In the multivariable analyses, PWD was significantly associated with age (p<0.001) and height (p<0.001), with an adjusted regression coefficient (95% CI) of 0.29 ms/years (0.23 to 0.36) and 0.32 ms/cm (0.28 to 0.37), respectively. PWD, given thereafter in ms with adjusted mean±SE, was significantly (p<0.05) associated with (a) gender (woman 110.0±0.4; man 112.1±0.4), (b) body mass index (normal 110.1±0.4; overweight 110.9±0.4; obese 113.0±0.5), (c) abdominal obesity (no 110.5±0.3; yes 111.7±0.4) and (d) hypertension (no 110.4±0.3; yes 111.7±0.4).Conclusion PWD is positively associated with age, height, male gender, obesity markers and hypertension. Clinical interpretation of PWD should take these factors into consideration.